2021
DOI: 10.7759/cureus.15598
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Single-Fraction Lung Stereotactic Ablative Radiotherapy in a Multicenter Provincial Cancer Program During the COVID-19 Pandemic

Abstract: BackgroundDuring the novel coronavirus disease 2019 (COVID-19) pandemic, cancer centers considered shortened courses of radiotherapy to minimize the risk of infectious exposure of patients and staff members. Amidst a pandemic, the process of implementing new treatment approaches can be particularly challenging in larger institutions with multiple treatment centers. We describe the implementation of single-fraction (SF) lung stereotactic ablative radiotherapy (SABR) in a multicenter provincial cancer program. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“… 4 Among both operable and inoperable patients, stereotactic body radiation therapy (SBRT) has been found to have high overall survival (OS) and local control with low toxicity rates. 5 , 6 , 7 , 8 , 9 , 10 Multiple studies have found SBRT to have comparable outcomes with surgical resection in early stage NSCLC, with the added benefit of noninvasiveness and stable quality of life. 5 , 11 , 12 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 Among both operable and inoperable patients, stereotactic body radiation therapy (SBRT) has been found to have high overall survival (OS) and local control with low toxicity rates. 5 , 6 , 7 , 8 , 9 , 10 Multiple studies have found SBRT to have comparable outcomes with surgical resection in early stage NSCLC, with the added benefit of noninvasiveness and stable quality of life. 5 , 11 , 12 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…Despite excellent outcomes and decreased cost, lack of familiarity among institutions remains a barrier to the widespread adoption of SF-SBRT in routine practice. 8 , 18 , 19 , 20 , 21 , 22 Increased utilization of SF-SBRT during the coronavirus disease 2019 pandemic has proven to be a cost-effective and practical solution to increase treatment compliance in patients with lung cancer. 21 , 23 , 24 Data regarding long-term outcomes with SF-SBRT in real-world clinical practice are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this evidence, prior to and even during COVID-19, adoption of single-fraction SBRT was modest [17][18][19]. Potential explanations include: lack of familiarity with the evidence and lack of clarity about the expected toxicity [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this superiority of SBRT, the treatment time for SBRT is much shorter with only a single-fraction schedule required for so-called stereotactic radiosurgery (SRS). Although the outcomes of SRS for early stage lung cancer or metastatic lung cancer have gradually been accumulating, the number of institutes in which SRS is performed is small [ 2 , 3 , 4 ]. In the RTOG 0915 trial in which 34 Gy in 1 fraction was compared to 48 Gy in four fractions for early stage lung cancer, the 34-Gy SRS arm showed lower rates of severe toxicities with primary control rates comparable to those of the 48-Gy SBRT arm [ 5 ].…”
Section: Introductionmentioning
confidence: 99%